2019
DOI: 10.1111/ijsa.12239
|View full text |Cite
|
Sign up to set email alerts
|

Affective and effective: Military job performance as a function of work‐related emotional intelligence

Abstract: The military is a highly stressful career that requires one to work closely with others. These features of the military render it plausible that skills related to emotional perception and management—or emotional intelligence—would tend to benefit performance within this setting. Hypotheses of this type were examined in a panel study that presented 152 active duty military personnel with a new scenario‐based measure that specifically focused on emotional occurrences within the workplace. As hypothesized, work‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 67 publications
(146 reference statements)
1
19
0
1
Order By: Relevance
“…We selected a sample of experienced professionals involved in the recruitment process for more than 1 year from a panel owned by a specialized company. Online panel data are increasingly being used to obtain convenience samples in market research and organizational studies (Bowling & Lyons, ; Bruk‐Lee et al, ; Djurdjevic, Rosen, Conroy, Rawski, & Sosna, ; Krishnakumar, Perera, Persich, & Robinson, ). We contracted Creatests®, a panel that contains 450,143 French participants, and works with a large number of companies and major universities and provides a high level of quality control.…”
Section: Methodsmentioning
confidence: 99%
“…We selected a sample of experienced professionals involved in the recruitment process for more than 1 year from a panel owned by a specialized company. Online panel data are increasingly being used to obtain convenience samples in market research and organizational studies (Bowling & Lyons, ; Bruk‐Lee et al, ; Djurdjevic, Rosen, Conroy, Rawski, & Sosna, ; Krishnakumar, Perera, Persich, & Robinson, ). We contracted Creatests®, a panel that contains 450,143 French participants, and works with a large number of companies and major universities and provides a high level of quality control.…”
Section: Methodsmentioning
confidence: 99%
“…Such feelings, when present, can be particularly challenging to individuals who are not able to regulate their feelings effectively (Ohly, 2018) or who become overwhelmed in the context of their negative affective feelings (Gohm, 2003). By contrast, the skills linked to EI, which include capacities to regulate one's negative affect (Pena-Sarrionandia et al, 2015), should support better performance in employee contexts in which negative feelings arise (Krishnakumar et al, 2019). Such regulatory operations were emphasized by Parke et al (2015), who found that EI helped employees regulate problematic states in a manner conducive to creative performance.…”
Section: Studymentioning
confidence: 99%
“…Under the contingency leadership theory, managers harness both objective and subjective measures and modify their behaviors to adjust their leadership style to match their contextual environment (Meng, 2016). Krishnakumar et al (2019) discussed the contingency leadership theory, noting that leaders under this theory will recognize the situations they find themselves in and adjust their leadership styles and behaviors to maximize their efficiency and effectiveness. Sometimes, the leader utilizing contingency leadership will adapt their leadership style to accommodate their followers to maximize their effectiveness and efficiencies.…”
Section: Theoriesmentioning
confidence: 99%
“…Contingency leadership theory. Krishnakumar et al (2019) indicated that the contingency leadership theory indicates that leaders can increase their effectiveness if they can adjust their leadership style or behaviors in response to any given situation. Some of the personnel observed during the field study exemplified the contingency leadership theory.…”
Section: Relationship Of Findings To the Research Frameworkmentioning
confidence: 99%